(untitled) - Delancey, George (Hoboken, New Jersey, 2013)
This book provides an introduction to chemical engineering topics in an integrated fashion and illustrates the methodology of process design through the processes followed in the text. It provides an all-in-one coverage of topics from process plant interactions to economic analyses and thermodynamic properties of streams. The book facilitates the students’ execution of process analysis and plant design in an orderly and logical fashion. This book serves as a good introduction and can act as a stepping stone for students interested in the traditional chemical engineering subjects
Keywords: Chemical engineering,Kỹ thuật hóa học